Analysis of Risk Factors for Anemia in Pregnant Women in the Working Area of ​​the Soe City Health Center, South Central Timor Regency: Analisis Faktor Risiko Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Kota Soe Kabupaten Timor Tengah Selatan - Rambadeta, Rina Djawa; Sakke Tir, Deviarbi; Ndoen, Honey Ivon; Tedju Hinga, Indriati A. (Universitas Mohammad Husni Thamrin, 2025)
Background: Anemia is a condition where there is a lack of red blood cells (erythrocytes) in the blood circulation or a low hemoglobin mass that is unable to fulfill its function as an oxygen carrier to all tissues. Purpose: This study aims to analyze the relationship between several risk factors and the incidence of anemia in pregnant women in the Soe City Health Center Working Area, South Central Timor Regency. Method: This study is an analytic observational study using Case Control design. This study was conducted at the Soe City Health Center in May 2024. The population in this study were all 785 pregnant women. The sample in this study amounted to 130 respondents with a ratio of 1:1, namely 65 respondents from the case group and 65 respondents from the control group, data collection was carried out using interview techniques to 130 respondents using random sampling techniques. Results: The results showed that maternal age did not have a significant relationship with the incidence of anemia in pregnant women (p=0.661; OR=1.212), parity had a significant relationship with the incidence of anemia in pregnant women (p=0.007; OR=2.348), adherence to taking Fe tablets had a significant relationship with the incidence of anemia in pregnant women (p=0.000; OR=256.000), frequency of ANC visits had a significant relationship with the incidence of anemia in pregnant women (p=0.000; OR=114.750), education had no significant relationship with the incidence of anemia in pregnant women (p=1.000; OR=1.000), and economic level had a significant relationship with the incidence of anemia in pregnant women (p=0.000; OR=10.141).